Effect of Usefulness Dimensions on Agricultural Markets - Budiastuti, Evrina; Ritchi, Hamzah; Deliana, Yosini (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2023)
With the largest population in Indonesia, Bogor Regency in West Java Province has agricultural potential. One of the prospective regions in Region V with agricultural populations that grow both fresh and processed agricultural products, from rural to urban. Problems in the promotion of agricultural products were discovered by the Government of Bogor Regency through the Agricultural Extension Center of Region V. To solve these issues, a platform called Kiosagri.com in the form of a marketplace has been introduced. It is required to quantify usability, which is influenced by the usability dimension, for this market to be useful. As a result, the purpose of this study is to examine the usability factors that influence the usability of the farmers that utilize the Kiosagri.com agricultural marketplace. This reserach employs a cross-sectional survey design and a quantitative methodology. Farmers who have been introduced to Kiosagri.com were the only respondents in the census. 32 respondents' data were analyzed using multiple linear regression tests and descriptive statistics. The findings demonstrated a substantial relationship between usability and the usability factors of learnability, efficiency, memorability, error, and satisfaction. Only efficiency, which has a substantial impact on usability, is the dimension that dominates this relationship.